Evaluation and management of the first unprovoked seizure in children: Single-center experience first unprovoked seizure in children - Dedeoglu, Ozge; Ardicli, Didem (Annals of Medical Research, 2022)
Aim: We aimed to evaluate clinical and laboratory features in children who presented unprovoked seizure for the first time and also to determine possible risk factors for seizure recurrence. Materials and Methods: A total of 219 patients (113 female, 106 male) presented with first unprovoked seizure were included in the study. Demographic, clinical findings (type and duration of seizures, seizure recurrence, antiseizure drugs), neuroimaging findings and electroencephalography (EEG) results were recorded retrospectively.Results: Median age of the patients was 30 months (IQR 12-66). A history of birth hypoxia and/or phototherapy and family history of epilepsy were present in 21% and 17.4%, respectively. Generalized seizures were the most common seizure type (42%), with a predominance at 2 years of age (p
Keywords: First unprovoked seizure; Antiepileptic management; Childhood epilepsy